2019
DOI: 10.1002/pmrj.12243
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Body Mass Index on Pulmonary Related Debility Rehabilitation

Abstract: Background Obesity is a known factor for the development of abnormal respiratory physiology. However, several studies have found that obesity does not hinder functional recovery in patients hospitalized for postacute care following a stroke or cardiovascular event. This study was designed to determine the effect of overweight and obesity on patients with acute pulmonary disease, hospitalized in an inpatient rehabilitation facility (IRF). Objective To investigate the impact of body mass index (BMI) on indices o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…In other neurological cohorts, studies have found that, among patients with stroke admitted to an IRF, those who are overweight and obese actually progress in function more quickly than do those who are normal weight. Further data in the IRF suggest a lack of ill effect of overweight or obese in IRF treatment of patient IRF treatment for primary pulmonary or cardiac related debility, as well as amputees …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other neurological cohorts, studies have found that, among patients with stroke admitted to an IRF, those who are overweight and obese actually progress in function more quickly than do those who are normal weight. Further data in the IRF suggest a lack of ill effect of overweight or obese in IRF treatment of patient IRF treatment for primary pulmonary or cardiac related debility, as well as amputees …”
Section: Discussionmentioning
confidence: 99%
“…Further data in the IRF suggest a lack of ill effect of overweight or obese in IRF treatment of patient IRF treatment for primary pulmonary or cardiac related debility, as well as amputees. [24][25][26][27][28] Given that data from the general population have suggested a greater functional decline among those with elevated BMI, one could easily speculate that the admissions process could be altered by a reasonable concern that those with significant elevated BMI might not be able to recover sufficiently to warrant an admission to an acute care rehabilitation hospital. These patients might be redirected (or discharged) to other post-acute care facilities such as skilled nursing facilities, long-term acute care facilities, or nursing homes.…”
Section: Discussionmentioning
confidence: 99%
“…30 . Der Einfluss des BMI auf die Liegedauer in der FR wurde bereits beschrieben 31 32 . Auch hier ist zu beobachten, dass mit längerer FR – und auch höherem Ressourceneinsatz – im Schnitt ähnliche Zugewinne an Mobilität erreichbar sind 31 .…”
Section: Diskussionunclassified